INFLUENCING FACTORS OF LOYALTY: THE CASE OF CV JOHNSON FARM - Sunanta, Grace Rosaline; Aprianingsih, Atik (Journal of Business and Management, 2017)
Abstract. Loyalty is a deep commitment to repurchase or subscribe to a product or service consistently in the future. It is not easy to retain customers loyalty in the increasing intensity of competition. Loyalty have a strong influence to a company’s survivability, including for a Business to Business (B2B) company such as CV Johnson Farm.  The purpose of this study is to investigate factors that influence the customer’s loyalty of CV Johnson Farm customers. Respondents for this study are business partners of CV Johnson Farm.The method that the researcher use is the quantitative method. Questionnaire was distributed to 32 respondents of CV Johnson Farm. Further, the data were analyzed using multiple linear regression. The result shows that relationship satisfaction and trust are positively and significantly related to loyalty. Thus, in order to increase the loyalty of CV Johnson Farm business customer, CV Johnson Farm needs improvement in their relationship satisfaction and trust. Key Words: Customer Loyalty, B2B Market, Service Quality, Relationship Satisfaction, Trust, Commitment.